Impact of nonpharmaceutical strategies on trends of COVID-19 in São Paulo State - Fortaleza, Cristiane Ravagnani; Vilches, Thomas Nogueira; Almeida, Gabriel Berg de; Ferreira, Claudia Pio; Souza, Lenice do Rosário de; Fortaleza, Carlos Magno Castelo Branco (Revista de Saúde Pública, 2021)
Interrupted time series analyses were conducted to measure the impact of social distancing policies (instituted on March 22, 2020) and of subsequent mandatory masking in the community (instituted on May 4, 2020) on the incidence and effective reproductive number of COVID-19 in São Paulo State, Brazil. Overall, the impact of social distancing both on incidence and Rt was greater than the incremental effect of mandatory masking. Those findings may reflect either a small impact of face masking or the loosening of social distancing after mandatory use of masks.